2019
DOI: 10.3390/ijerph16030338
|View full text |Cite
|
Sign up to set email alerts
|

Where Do Vapers Buy Their Vaping Supplies? Findings from the International Tobacco Control (ITC) 4 Country Smoking and Vaping Survey

Abstract: Aim: This study examines where vapers purchase their vaping refills in countries having different regulations over such devices, Canada (CA), the United States (US), England (EN), and Australia (AU). Methods: Data were available from 1899 current adult daily and weekly vapers who participated in the 2016 (Wave 1) International Tobacco Control Four Country Smoking and Vaping. The outcome was purchase location of vaping supplies (online, vape shop, other). Adjusted odds ratios and 95% confidence intervals were r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
31
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 23 publications
5
31
1
Order By: Relevance
“…A limitation of our study is the reliance on e-cigarettes sold through retail stores, thus we cannot capture e-cigarettes sold through specialty vape shops and online. One study estimates that in 2015, 40% of e-cigarette sales occurred in retail stores similar to those we study in the NRSD (Levy et al 2019), and another study finds that in 2016 30% of U.S. adult vaporers purchased e-cigarettes in retail stores (Braak et al 2019). However, e-cigarette taxes are collected for both online and vape shop purchases in the same way they are collected in retail stores, so we are unaware of any reason why individuals would have a financial incentive to change the type of store where they shop in response to an e-cigarette tax.…”
Section: Resultssupporting
confidence: 73%
“…A limitation of our study is the reliance on e-cigarettes sold through retail stores, thus we cannot capture e-cigarettes sold through specialty vape shops and online. One study estimates that in 2015, 40% of e-cigarette sales occurred in retail stores similar to those we study in the NRSD (Levy et al 2019), and another study finds that in 2016 30% of U.S. adult vaporers purchased e-cigarettes in retail stores (Braak et al 2019). However, e-cigarette taxes are collected for both online and vape shop purchases in the same way they are collected in retail stores, so we are unaware of any reason why individuals would have a financial incentive to change the type of store where they shop in response to an e-cigarette tax.…”
Section: Resultssupporting
confidence: 73%
“…Patterns are similar among young adults. A national survey found that only 24% of vapers aged 18–24 bought their e-cigarettes at retail, the lowest among all adult age groups, while 48% purchased at a vape shop 19. The e-cigarette price measure used in our study was constructed using retail store sales data, which may not accurately capture the costs of e-cigarettes used by young people and the wide range of products sold in vape shops.…”
Section: Discussionmentioning
confidence: 99%
“…In Canada (CA), where vape shops are the most commonly reported source of NVPs, ecigarettes containing nicotine have been technically illegal, although enforcement has been weak, and new regulations that will permit the legal retail sale of NVPs are under consideration. The legal restrictions on the sale of NVPs in CA have had the effect of keeping NVP devices (typically closed systems) manufactured by cigarette manufacturers out of retail shops, while NVP devices manufactured by non-cigarette companies (typically open systems) dominate the market [12]. Government regulators are increasingly being asked to develop standards that address the safety, labelling and nicotine delivery of NVPs [13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%